Performance Analysis of Tray Dryer to Reduce the Drying Process Time of Cayenne Pepper - khoryanton, Ampala; Yanuar, Padang; Saputro, Raynaldi; Supandi, Supandi (Politeknik Negeri Semarang, 2022)
Chili is a type of vegetable that is easily damaged and difficult to maintain in fresh form. The durability of fresh chilies if stored at low temperatures can last up to 14 days, but if stored at room temperature chilies only last about 2-4 days. Because of this, chili prices are always erratic, when chili prices are low, farmers will overcome losses by drying chilies using natural methods of sunlight. This method is considered less effective because it requires a large drying area and relatively long drying time. Therefore, it is necessary to manufacture and test chili drying ovens to speed up the drying process time and increase the durability of chilies. This research method focuses on the process of testing the performance of the drying oven. The test parameter used is using temperature of 70â„ƒ with 3 variations of drying process time, namely 6 hours, 7 hours, and 8 hours to produce dry chili water content according to the standard, which is a maximum of 11%. The results of the chili drying oven research are the best drying time for 8 hours with a temperature of 70â„ƒ which produces a water content of 9.33% cayenne pepper. In addition, the drying oven testing process resulted in a drying efficiency of 35.4%.